Schools of Government’s roles and challenges for institutionalization: a comparative study in the Brazilian Federal Public Sector - Fonseca, Diogo Ribeiro da; Camões, Marizaura Reis de Souza; Cavalcante, Pedro Luiz Costa; Lemos, Joselene; Palotti, Pedro Lucas de Moura (Revista do Serviço Público, 2019)
The role of Schools of Government has been relatively vague in the literature and in several countries’ public administrations. Consequently, schools operate in normative contexts that do not address their specific needs and purposes as educational entities. The present study seeks to comparatively describe institutional, strategic and educational characteristics of 17 Brazilian Federal Schools of Government to define aspects for their distinctive characterization. The qualitative research was based in document analysis and structured interviews with heads in schools. The results present a common identity between schools, as well as differences regarding their configurations. We attempt to propose a typology for the sampled schools which, we suggest, may be used as a means for a general theory for the comprehension of varying characteristics between schools of government, relating to their roles and formats. The study contributes to a better understanding regarding the role of schools of government and proposes further research to support their institutionalization and development.